Ocupação e detecção de Callicebus nigrifrons e Callithrix aurita em fragmentos de Mata Atlântica no Sul de Minas Gerais - Silva, Nilmara Cristina da (2017)
The Atlantic Forest has a high diversity, a high degree of endemism and at the same time is one of the most threatened biomes in the Planet, being considered a conservation hotspot. The major threats to global biodiversity include fragmentation and habitat loss, but different species respond in different ways to changes in the environment. Understand the fauna and flora responses against changes in the environment is important for conservation actions. The main goal of this study was evaluate the probabilities of occupancy and detection of two primates (Callicebus nigrifrons and Callithrix aurita) in 23 fragments in the Atlantic Forest, Southern of Minas Gerais, and verify if variables could influence the species occupancy. The method of playback was used as a way of sampling the primates. The occupancy of both species was high, and for Callicebus nigrifrons was superior, and none of the variables obtained a possible explanation for the occupancy of the species in the fragments sampled. The detectability of Callicebus nigrifrons was quite high, being a highly responsive species to the playback. For Callithrix aurita, the size of the area was the most influential variable in the occupancy of the species, and in smaller areas the occupancy is higher. The high occupancy of the species by smaller areas can be explained by their preference for altered and border environments, as well as for their low detectability, being a cryptic species, naturally rare, it is difficult to detect it in larger areas. The results show that the small fragments also have importance in the maintenance of species, which should be considered in biodiversity conservation plans.